2019
DOI: 10.1186/s12902-019-0447-3
|View full text |Cite
|
Sign up to set email alerts
|

Participatory learning and action to address type 2 diabetes in rural Bangladesh: a qualitative process evaluation

Abstract: BackgroundDiabetes is 7th largest cause of death worldwide, and prevalence is increasing rapidly in low-and middle-income countries. There is an urgent need to develop and test interventions to prevent and control diabetes and develop the theory about how such interventions can be effective. We conducted a participatory learning and action (PLA) intervention with community groups in rural Bangladesh which was evaluated through a cluster randomised controlled trial. There was a large reduction in the combined p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 50 publications
4
28
1
1
Order By: Relevance
“…However, people were also selective about the messages they shared with others, and perceived messages delivered in group discussions to be inherently more valuable and trustworthy than those delivered by mobile messages. This resonates with findings from the qualitative process evaluation of the DMagic trial that the group discussions gave confidence to members of the community who were illiterate and that their credibility was heightened with others in their community if they had attended a group meeting (Morrison et al, 2019). This points to the role of group and community interactions in the way individuals perceive the value of their own individual actions and behaviors (Howarth et al, 2004).…”
Section: Perceived Benefits Of Group Interventions For Message Dissemsupporting
confidence: 61%
See 2 more Smart Citations
“…However, people were also selective about the messages they shared with others, and perceived messages delivered in group discussions to be inherently more valuable and trustworthy than those delivered by mobile messages. This resonates with findings from the qualitative process evaluation of the DMagic trial that the group discussions gave confidence to members of the community who were illiterate and that their credibility was heightened with others in their community if they had attended a group meeting (Morrison et al, 2019). This points to the role of group and community interactions in the way individuals perceive the value of their own individual actions and behaviors (Howarth et al, 2004).…”
Section: Perceived Benefits Of Group Interventions For Message Dissemsupporting
confidence: 61%
“…The group also strengthened their social network, which enabled them to collectively interact with others to change behaviors. Both the VPA and process evaluation research showed that the groups addressed social norms, creating an enabling social context within the household and community to enact healthy behaviors ( Morrison et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will conduct a mixed methods process evaluation following the UK Medical Research Council guidelines to describe the intervention implementation and develop the theory of how the intervention can affect health outcomes in this context [ 25 ]. The intervention and trial design has used the extensive formative and process evaluation research from the DMagic trial [ 18 , 19 ]. A process evaluation officer will collect qualitative data on how the intervention is working through (1) group observations throughout the intervention and (2) semi-structured and key informant interviews and group discussions in case study communities at two time points during the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…A process evaluation officer will collect qualitative data on how the intervention is working through (1) group observations throughout the intervention and (2) semi-structured and key informant interviews and group discussions in case study communities at two time points during the intervention. We will develop our hypothesis that health literacy is improved by the intervention [ 19 ] by integrating questions on health literacy in our survey tools [ 26 ]. We will also develop our hypothesis about the intervention effect on diabetes stigma through qualitative research and four quantitative questions asked to self-reported diabetics in the individual questionnaires.…”
Section: Methodsmentioning
confidence: 99%